Structural and mechanical characterization of hybrid metallic-inorganic nanosprings. (16th October 2017) - Habtoun, Sabrina; Houmadi, Said; Reig, Benjamin; Pouget, Emilie; Dedovets, Dmytro; Delville, Marie-Hélène; Oda, Reiko; Cristiano, Fuccio; Bergaud, Christian
Abstract: Silica nanosprings (NS) are fabricated by a sol–gel deposition of silica precursors onto a template made of self-assembled organic chiral nanostructures. They are deposited and assembled on microstructured silicon substrates, and then metallized and clamped in a single lithography-free step using a focused ion beam (FIB). The resulting suspended hybrid metallic/inorganic NS are then characterized with high-resolution transmission electron microscopy (HRTEM) and scanning TEM/energy-dispersive X-ray spectroscopy (STEM/EDX), showing the atomic structure of the metallic layer. Three-point bending tests are also carried out using an atomic force microscope (AFM) and supported by finite element method (FEM) simulation with COMSOL Multiphysics allowing the characterization of the mechanical behavior and the estimation of the stiffness of the resulting NS. The information obtained on the structural and mechanical properties of the NS is discussed for future nano-electro-mechanical system (NEMS) applications.